EDUCATION INTITUTION MANAGEMENT AND DEVELOPMENT STRATEGY ON CENTRE OF MEDICAL SPECIALIST EDUCATION PROGRAM FACULTY OF MEDICINE HASANUDDIN UNIVERSITY, MAKASSAR - Arisakti, Aldian; Brasit, Nurdin; Wahda (Journal of Business Issues, 2023)
This research aims to determine the management and development strategy of educational institutions at the center of the specialist medical education program at Hasanuddin University's medical faculty. The analytical tool used in this research is SWOT analysis. The results of the research state that strategic planning in improving the quality of education is a design of activities to follow up on previous programs after program evaluation. programs to improve the quality of education reflect the vision, mission and objectives of PPDS FK Unhas. The guideline for creating a program to improve the quality of education, in this case PPDS FK Unhas, is to provide facilities to lecturers and human resources at PPDS FK Unhas, one example is by facilitating lecturers in conducting research. In carrying out activities to improve the quality of education at PPDS FK Unhas, there are several obstacles faced, one of which is the lack of specialist staff in areas of need.